Musculoskeletal disorders, stress perception and physical activity in police officers - Maysa Venturoso Gongora Buckeridge Serra; João Domingos Scalon; Maria Georgina Marques Tonello; Paulo Roberto Veiga Quemelo (Universidade de São Paulo, 2020)
ABSTRACT The purpose of this study is to analyze association between stress perception and physical activity with the prevalence of symptoms of musculoskeletal disorders (SMSD) in police officers. The police officers (n=142) answered the Perceived Stress Scale-10 (PSS-10) and the Nordic Musculoskeletal Questionnaire. Pearson's linear correlation coefficient was used to measure strength and direction of relationship between PSS-10 and prevalence of SMSD and showed a positive correlation between variables in the last 7 days (r=0.34, p=0.00001) and in the last 12 months (r=0.40, p=0.00001). The mean prevalence of SMSD in the last 12 months was lower among police officers practicing physical activity (W=1888.5, p=0.04). Multiple logistic regression analysis showed that the practice of physical activities as well as efforts to reduce stress perception both decrease the odds of musculoskeletal disorders. This study indicated that stress level and physical activity practice influenced in prevalence of SMSD. Multidisciplinary interventions with actions to reduce stress level and encourage physical activity practice are needed to control SMSD prevalence.